An Exploration of Jamaican Mothers’ Perceptions of Closeness and Intimacy in the Mother–Child Relationship during Middle Childhood - Burke, Taniesha; Kuczynski, Leon; Perren, Sonja (Frontiers in Psychology, 2017)
Research on Jamaican mother–child relationships has had a limited focus on authoritarian parenting styles and selected discipline practices such as corporal punishment. This study examined Jamaican mothers’ experiences of closeness and connectedness with their children to provide a holistic perspective on Jamaican-parent–child relationships. Thirty mothers (17 middle class and 13 lower class) living in Kingston and St. Andrew, Jamaica, participated in a 1-h to 1.5-h semi-structured, open-ended interview regarding their 8- to 12-year-old children. Thematic analyses indicated that mothers experienced closeness through intimate interactions (e.g., shared projects, shared physical affection, mutuality, and child self-disclosure) and parent–child nurturance. Both mothers and children were active in creating contexts for closeness. Mothers also reported experiences that temporarily damaged their connection with their children. The findings suggest that the construct of parent–child intimacy may be useful in teasing out the psychological meanings and interpersonal processes of parent–child relatedness in cultural research.